The Role of Nonstandard Workers in Client-Organizations - Olsen, Karen (Relations industrielles / Industrial Relations, 2006)
This paper examines the diversity and complexities of nonstandard work. Two types of nonstandard workers are studied: workers employed by temporary help agencies (THAs) and contract company workers, both of which are involved in a triadic employment relationship. The analyses are based on interviews with managers in three service-sector companies in Norway. The paper discusses the dilemmas managers in client-organizations face when agency temporaries and contract company workers are integrated and do work similar to what is done by the regular workers in the firm. Managers in client-organizations require loyalty from nonstandard workers, and under certain conditions, nonstandard workers are able to form pressure groups. The findings are discussed in relation to the highly regulated labour market in Norway, in a period of labour shortage.